Seeking Justice at the Court of the Khans of Khiva (19th - early 20th Centuries) - Sartori, Paolo (Brill's Inner Asian Library, 2020)
In Seeking Justice at the Court of the Khans of Khiva, Sartori and Abdurasulov show that in Khorezm prior to Sovietization the dispensation of justice according to Islamic law depended mostly on a group of officials representing the dynasty in power, and lacking specialised legal training.; Readership: All interested in the history of Islamic Central Asia and Islamic law